MiR-21 and let-7 cooperation in the regulation of lung cancer - Bai, Jinquan; Shi, Zhenzhou; Wang, Shuting; Pan, Hong; Zhang, Tong (Frontiers in Oncology, 2022)
Background Lung cancer occurs and develops as a result of a complicated process involving numerous genes; therefore, single-gene regulation has a limited therapeutic effect. We discovered that miR-21 expression was high in lung cancer tissues and cells, whereas let-7 expression was low, and it is unclear whether their combined regulation would be superior to therapy involving single regulation. The goal of our research was to investigate this situation and the regulatory mechanism that exists between these genes. Methods To regulate the levels of miR-21 and let-7 in these two types of lung cancer cells, we transfected miRNA mimics or inhibitors into A549 and H460 cells. Lung cancer cells were tested for proliferation, apoptosis, migration, and invasion. The results were verified using a Western blot and a qRT-PCR assay. Bioinformatics was used to investigate their potential regulatory pathways, and luciferase assays were used to confirm the binding sites. Results The expression of miR-21 was increased and that of let-7 was decreased in lung cancer tissues and cells compared with paracancerous tissues and normal lung cells (p < 0.01). Tumor cells were inhibited by downregulation of miR-21 and upregulation of let-7, and cooperative regulation showed a better effect. Upregulation of miR-21 and downregulation of let-7 promoted tumor cells, and this tumor-promoting effect was amplified by cooperative regulation. MiR-21 regulated lung cancer cells directly via the Wnt/-catenin pathway, and let-7 exerted its effects via the PLAG1/GDH1 pathway. MiR-21 and let-7 cooperated to regulate lung cancer cells via the K-ras pathway. Conclusions The effect of cooperative regulation of miR-21 and let-7 on lung cancer is greater than that of a single miRNA. MiR-21 and let-7 are important differentially expressed genes in lung cancer that are regulated by the K-ras pathway. As a result, for multigene lung cancer, the cooperative regulation of two miRNAs will provide a new target and direction for lung cancer treatment in the future.